Pelatihan Penyusunan Materi Ajar Terintegrasi Teknologi Bagi Guru di SMPN 19 Mataram - Rahmawati, Lela; Miswaty, Titik Ceriyani; Anggrawan, Anthony; Purnama, Baiq Kartika (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
From the amount of data obtained on the number of teachers teaching at SMPN 19 Mataram, the situation of the learning process was analyzed. Learning at SMPN 19 Mataram mostly still uses manual materials using printed books. For this reason, this training was deemed necessary so that SMPN 19 Mataram teachers could make technology-integrated teaching materials. One of the technologies that can support teaching materials especially in teaching students achievement in the field of English is the Powtoon Program. This application is a web-based animation software that allows users to quickly and easily create animated presentations by manipulating pre-made objects, imported images, provided music, and user-generated voiceovers. Powtoons are used by businesses to create attractive and creative presentations that attract attention, and can also be used for educational assessments and content delivery. PowToon is a tool similar in operation to Power Point, Impress, or even Prezi. It uses a slide on which text and images can be added, but also allows animation and the incorporation of sound or music, available within the same application or via an external source.